Potential Implications of Angiotensin-converting Enzyme 2 Blockades on Neuroinflammation in SARS-CoV-2 Infection - Suresh Mohankumar (Current Drug Targets, 2022)
Angiotensin-converting enzyme 2 (ACE2) has been reported as a portal for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Consequently, scientific strategies to combat coronavirus disease of 2019 (COVID-19) were targeted to arrest SARS-CoV-2 invasion by blocking ACE2. While blocking ACE2 appears a beneficial approach to treat COVID-19, clinical concerns have been raised primarily due to the various intrinsic roles of ACE2 in neurological functions. Selective reports indicate that angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) upregulate ACE2 levels. ACE2 metabolizes angiotensin II and several peptides, including apelin-13, neurotensin, kinetensin, dynorphin, [des-Arg9] bradykinin, and [Lys-des-Arg9]-bradykinin, which may elicit neuroprotective effects. Since ARBs and ACEIs upregulate ACE2, it may be hypothesized that patients with hypertension receiving ARBs and ACEIs may have higher expression of ACE2 and thus be at a greater risk of severe disease from the SARS-CoV-2 infections. However, recent clinical reports indicate the beneficial role of ARBs/ACEIs in reducing COVID-19 severity. Together, this warrants a further study of the effects of ACE2 blockades in hypertensive patients medicated with ARBs/ACEIs, and their consequential impact on neuronal health. However, the associations between their blockade and any neuroinflammation also warrant further research. This review collates mechanistic insights into the dichotomous roles of ACE2 in SARS-CoV-2 invasion and neurometabolic functions and the possible impact of ACE2 blockade on neuroinflammation. It has been concluded that ACE2 blockade imposes neuroinflammation. [Abstract copyright: Copyright© Bentham Science Publishers; For any queries, please email at epub@benthamscience.net.]